PENGEMBANGAN BAHAN AJARTRIGONOMETRI BERBASIS MOBILE LEARNING UNTUK KELAS X SMA/MA - Michel Rizaldi (Departemen Matematika, 2019)
The development of technology entered the era of the industrial revolution 4.0 has affected the field of education. Mobile learning is learning that utilize information and communication technology that can be accessed flexibly (anywhere, anytime). This research aims to develop teaching materials based mobile learning for the material trigonometry are valid and practical. This type of research is development research by adapting the model of Plomp consisting of the stage of the preliminary research and prototyping phase. The Preliminary stage of the research includes the analysis of needs, analysis of learners, curriculum analysis and the analysis of the concept. The Prototyping phase is the stage for designing teaching materials based mobile learning which consists of prototype 1, prototype 2, and prototype 3 were evaluated using a design of formative evaluation . The results showed that teaching material based mobile learning that is produced is valid and practical.Keywords – Mobile Learning, Trigonometry,Teaching Material